PENGARUH PDRB DAN UKURAN TERHADAP INTERNAL CONTROL PEMERINTAH DAERAH DENGAN PAD SEBAGAI INTERVENING - Wardoyo Putro, Prima Utama (STIE AUB Surakarta, 2018)
Law No 32 year on 2004 about Regional Government and Law No 33 years on 2004 about Fiscal Balance between the Central Government and Regional Government are a new regulation relating to the implementation of regional autonomy in Indonesia. Giving the authority to manage its own region required an internal control system that can monitor of all by central government. The problem in this study is: Is there are any influence between growth, size, and PAD through Regional Government Internal Controls weakness with PAD as an intervening variable. The research populations are the financial statements and reports on the results of the entire province in Indonesia totaling 33 provinces. Source of data which are used are secondary data, and data collection by using the documentation method. The results of partial testing showed that PAD and Growth have significant affects to the Internal Controls, whereas size has not significant effect. Simultaneous testing showed a significant effect between the independent and dependent variables. The test results path testing showed that growth has no significant effect to internal control through PAD as an intervening variable and size has a significant effect to internal control variable through PAD as an intervening variable. The results of determinant coefficient by simultan test amount 28.7%. Its mean that Internal Control can be explained by Growth, Size and PAD, the remaining 71.3% influenced by factors other than study.Â Keyword: Internal Control, Size, Growth, and Income